GAYA KEPEMIMPINAN BACHARUDDIN JUSUF HABIBIE PASCA ORDE BARU TAHUN 1998-1999 - Agung Mahar Rani; Muhammad Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Starting from President Suharto, who resigned in the middle of his reign, Habibie, who served as Vice President at the time. In accordance with the Act of 1945, replacing President Suharto. Rising Habibie became the number one in Indonesia provide a different color during the previous government, which virtually dominate the political scene for over 30 years. Leadership Style Habibie was considered able to change the national order of the nation, and can restore the confidence of the people against the people. Habibie was able to transform himself to share with followers in running the government.In looking at the relevant Habibie leadership style, the Transformational Leadership Theory allows to be used as the basis for this study. Through research technique Library Research Methods ( Studies Library ) can be seen through a short trip Habibie in his tenure in the Reformation era. Post- New Order government, leaving many tasks and problems from the east end to the west.With this kind of leadership style, Habibie piecemeal provide space for many people to be able to aspire to, express opinions in public, and give people the freedom to establish political organizations and others as the ideals of reform after the collapse of the new order.Keywords : Habibie, Transformational Leadership Style and Post- New Order.